Approaches to teaching cases in Slovene as a second and foreign language - Ulčnik, Natalija; Nikolovski, Gjoko (Slavia Centralis, 2021)
Many students of Slovene as a second and foreign language, whose mother tongue is an analytical language, have a vague concept of cases and declensions. This is why it is necessary to familiarise them with both concepts by using a teaching approach that will enable them to learn cases and declensions along with all their peculiarities more easily. On the basis of theoretical grounds and teaching practice, the article highlights one possible approach to teaching cases in Slovene.
Keywords: morphology; case; Slovene; foreign language; learning approach